Analisis Kebutuhan Kipas Untuk Sistem Air Flow Tambang dalam Pt Bukit Asam TBK Unit Pertambangan Ombilin - Dwi Wahyu Ningsih; Aris Susilo; Rodiyah Nursani (International Forum of Researchers and Lecturers, 2026)
The ventilation system is a critical factor in underground mining operations, ensuring the availability of fresh air and the dilution of hazardous gases for workers. This study will be conducted at PT Bukit Asam Tbk’s Ombilin Mining Unit (UPO) and will focus on analyzing fan requirements to optimize the airflow system. The issues addressed in this study include the imbalance between the supplied air volume and the size of the working area, as well as the potential for methane (CH₄) and carbon monoxide (CO) accumulation. The research methodology involves direct field measurements of ventilation parameters- such as air velocity, airway cross-sectional area, humidity, and gas concentration levels. The collected data will be processed mathematically to calculate total fresh air requirements based on the number of workers, machinery, and occupational health standards. The study aims to provide technical recommendations regarding the appropriate specifications and placement of fans (both main and auxiliary) to create a safe and productive working environment in compliance with applicable mining safety regulations.